2001
DOI: 10.4049/jimmunol.167.9.5004
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Phagocytosis of Apoptotic Inflammatory T Cells Leads to Down-Regulation of Microglial Immune Activation

Abstract: Apoptotic cell death is an established mechanism to terminate an inflammatory response in rodent or human brains. Microglia, as the resident phagocyte, is a strong candidate for the clearance of apoptotic lymphocytes. Apoptosis was induced in cultured autologous thymocytes and in myelin basic protein (MBP)-specific, encephalitogenic T cells from Lewis rats by the addition of 0.1 μg/ml methylprednisolone. The amount of phagocytosis of apoptotic cells was assessed using an in vitro phagocytosis assay. Supernatan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
63
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(68 citation statements)
references
References 57 publications
4
63
0
1
Order By: Relevance
“…Several authors have indicated that microglial activation following neuronal injury represents mainly a protective mechanism that limits further neurodegeneration (Minghetti and Levi 1998;Streit et al 1999;Polazzi and Contestabile 2002). Indeed, it has been shown that phagocytosis of apoptotic cells by microglia decreases the production of pro-inflammatory cytokines, such as TNF-α and IL-12, without affecting the secretion of anti-inflammatory and potentially neuroprotective molecules, such as IL-10 and TGF-ßl (Magnus et al 2001). It has also been demonstrated that microglia releases molecules able to rescue neurons from apoptotic death and, in turn, diffusible signals from apoptotic neurons enhance the neuroprotective properties of microglia (Polazzi et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have indicated that microglial activation following neuronal injury represents mainly a protective mechanism that limits further neurodegeneration (Minghetti and Levi 1998;Streit et al 1999;Polazzi and Contestabile 2002). Indeed, it has been shown that phagocytosis of apoptotic cells by microglia decreases the production of pro-inflammatory cytokines, such as TNF-α and IL-12, without affecting the secretion of anti-inflammatory and potentially neuroprotective molecules, such as IL-10 and TGF-ßl (Magnus et al 2001). It has also been demonstrated that microglia releases molecules able to rescue neurons from apoptotic death and, in turn, diffusible signals from apoptotic neurons enhance the neuroprotective properties of microglia (Polazzi et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Not only is the clearance of such cellular debris an important function of tissue phagocytes, making it an appealing hypothesis to suggest that phagocyte number should be linked to the amount of debris awaiting clearance, but more recently a molecular mechanism to explain such a link has been uncovered. Huynh and coworkers (50) demonstrated that macrophages secrete the cytokine TGF-␤ upon taking up apoptotic bodies, at least in the lung and peritoneum, although a different mechanism seems to be operative in brain (51). Since TGF-␤ is a major anti-inflammatory cytokine acting to suppress monocyte recruitment into a range of tissues (52), this provides a mechanistic link between apoptotic clearance and macrophage numbers: if uptake of apoptotic bodies is impaired, then TGF-␤ secretion will be reduced and macrophage numbers will increase.…”
Section: Discussionmentioning
confidence: 99%
“…They remove damaged structures such as apoptotic cells and obsolete synaptic connections from the extracellular space (Kreutzberg, 1996). Whereas the uptake of foreign material leads to microglial activation to engage an immunological response, ingestion of apoptotic bodies is associated with an anti-inflammatory reaction (Magnus et al, 2001). By contrast, endogenous molecules derived from injured or necrotic cells serve as danger signals to microglia Lehnardt et al, 2008).…”
Section: Discussionmentioning
confidence: 99%